Rzym – podróż służbowa .......... 303 - Wiącek, Elżbieta (Peregrynacje międzykulturowe: Księga jubileuszowa dedykowana prof. Tadeuszowi Palecznemu, 2025)
ROME – BUSSINESS TRIPThe text describes, in the form of a personal journal, the author’s journey to Rome in 2017 as part of the Erasmus+ teachers’ mobility program. The account of the stay includes impressions of social behaviors in tourist locations, particularly photographic practices, as well as reflections on the ontology of the image and the relationship between images and reality. The author also pays special attention to traces of the past and the place of migrants in the contemporary ethnoscape of the city.